Longitudinal Associations Between Bullying and Children's Preference for Television Violence - Hawa, Veronica (2013)
Abstract: The aim of this study was to examine the longitudinal associations between bullying and preference for violent television programs. A sixth-month, two time-point longitudinal design was used in order to identify the direction of the relation between bullying and preference for violent television programs. The participants were 417 sixth grade students of elementary schools in Cyprus. They completed the bullying subscale of the Revised Bullying and Victimization Questionnaire (BVQ-R) and the Preference for Television Violence Questionnaire (PTVQ). The findings of this study suggested a reciprocal relation between preference for violent TV programs and bullying. Specifically, bullying at Time1 positively predicted an increase in violent TV programs preference at Time 2. Similarly, preference for TV violence at Time1 positively predicted bullying at Time 2. We conclude that prior involvement in bullying may function as a risk factor for more future preference for violent programs on television and at the same time children who already prefer violent programs are more likely to manifest bullying in the future